Product-line instantiation guided by subdomain characterization: a case study - Pernich, Patricia (2012)
Reuse-oriented software methodologies have emerged to provide a set of rules or guides for development and evolution of software systems by reusing existing domain engineering artefacts such as requirements, architecture, components, test cases, etc. Domain engineering methods, such as software product lines engineering, aim at reducing development time, effort, cost, and complexity by taking advantage of the commonality within a portfolio of similar products. However, these methodologies are not based on specific domains, instead they cover a wide range of domains without considering particularities within them. Therefore, in this work we define a novel approach in which the creation of a software product line is guided by a subdomain analysis process, oriented to a particular case within the marine ecology domain. The methodology is then applied to a specific organization in order to create a product of the line.